Global Nutrition Report 2016: From Promise to Impact: Ending Malnutrition by 2030 - International Food Policy Research Institute; Haddad, Lawrence; Hawkes, Corinna; Udomkesmalee, Emom; Achadi, Endang; Bendech, Mohamed Ag; Ahuja, Arti; Bhutta, Zulfiqar; De-Regil, Luzmaria; Fanzo, Jessica; Fracassi, Patrizia; Grummer-Strawn, Laurence M.; et al. (International Food Policy Research Institute, 2016)
Few challenges facing the global community today match the scale of malnutrition, a condition that directly affects 1 in 3 people. Malnutrition manifests itself in many different ways: as poor child growth and development; as individuals who are skin and bone or prone to infection; as those who are carrying too much weight or whose blood contains too much sugar, salt, fat, or cholesterol; or those who are deficient in important vitamins or minerals. Malnutrition and diet are by far the biggest risk factors for the global burden of disease: every country is facing a serious public health challenge from malnutrition. The economic consequences represent losses of 11 percent of gross domestic product (GDP) every year in Africa and Asia, whereas preventing malnutrion delivers $16 in returns on investment for every $1 spent. The world’s countries have agreed on targets for nutrition, but despite some progress in recent years the world is off track to reach those targets. This third stocktaking of the state of the world’s nutrition points to ways to reverse this trend and end all forms of malnutrition by 2030.